(3efjI GdeMUdjf aj MbjbI WQjbI GdeLJgOjfs - (3GdMSjfj, GdbGSej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG, J (B1242 (3g`s
(3ChdgG (B:s
... (3gPg QSGdI JTJed Ydi eSGFd UGQJ eMdG ddNdGa Hjf GdYdeGA GdCYdGe heYQcI ddaVdGA ef Chdi GdCPgGf hGdCagGe Hjf GdeLJgOjf hGdENHGQjjf QVhGf Gddg Ydjge CLeYjf eY fbd COdI GdWQajf (B...s
(3BNQgG (B:s
... (3hPcQfG GdGOdI GdOGdI Ydi Pdc hGdeUQMI HeG gfGdc be bGd hEf Cecf GdefGbTI aj gPg GdaQhb adG jecf GdefGbTI ajgG cdgG Gh eLehYgG GfJgi hbO YQaJ Gf GcKQgG efGbT aj LYdg efGWG (B.. (3bO Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\131s
(3GdPQjYI (B23 - 130 (8655)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds